PANHYPOPITUITARISM AND CEREBRAL SALT WASTING IN A 19-YEAR-OLD FILIPINO MALE WITH ASEPTIC MENINGITIS: A CASE REPORT - Ng, Jennifer Lourdes; Ong-Ramos, Celeste (Journal of the ASEAN Federation of Endocrine Societies, 2023)
CASE A 19-year-old Filipino male had a fever, headache and decreased sensorium. Cranial MRI showed diffuse leptomeningeal enhancement without a discrete mass or hemorrhage. The sella was unremarkable. He had elevated opening pressure upon lumbar puncture. Ceftriaxone, anti-Koch’s, dexamethasone, and mannitol were started. He had severe hyponatremia (108 mg/dl) and seizure episodes. Workup showed low TSH (0.37 uIU/ml), fT3 (1.61 pg/ml), fT4 (0.82 ng/dl), and low serum cortisol (1.9 mg/dl). Additional hormone testing revealed low IGF-1 (102 ng/ ml), FSH (0.65 mIU/ml) and free testosterone (0.178 ng/ml = 2.96%). Dexamethasone was continued. Levothyroxine was started. His serum sodium improved with no recurrence of seizures. On the 3rd week, even after mannitol discontinuation, he became clinically dry, relatively hypotensive (90/60 mmHg), and hyponatremic (131 mg/dl) with increased urine output at 200–300 ml/hr. The workup showed serum osmolality of 287 mOsm/kg, elevated urine osmolality at 509 mOsm/kg, and elevated urine sodium of 187 mmol/L. He was given intravenous PNSS and 2% NaCl. He was also started on NaCl tablets and fludrocortisone. His serum sodium levels improved and his blood pressure normalized. He was eventually discharged stable.